Delay Circuits as Pulse Analysators - Hermanis, E. (Elektronika ir Elektrotechnika, 1997)
There are considered delay circuits with parallel outputs, the simultaneous instantaneous values of which are used as corresponding spectral coefficients in the signal expansions. There are analyzed and synthesized signal errors by the number of the expansion members and depending on the measuring precision of the instantaneous values. Delay circuits can be used in simultaneous pulse detection equipment without synchrosignals.